GAMBARAN PSYCHOLOGICAL WELL-BEING MENANTU LAKI-LAKI YANG TINGGAL BERSAMA MERTUA - Putri, Natasha Eka; Priadi, Mohammad Adi Ganjar (Atma Jaya Catholic University of Indonesia, 2024)
In Indonesia, there are number of people who choose to stay with their parents even though they already in a marriage. Some people experience this as a part of cultural tradition or based on other reasons. Living with in-laws requires maturity. This because living in the same house with in-laws can lead to conflict. If someone can manage, then living with in-laws is not a problem. However, if unable to cope, the conflict that occurs can have an impact for psychological well-being. Furthermore, stay with in-laws has advantages and disadvantages. For the advantages, couples can save money, especially for they who can't afford a house. On the contrary, living in the same house with in-laws also could be stressful to handle. There are some problems that appear related to the situation. This research aim is to gain about psychological well-being of son-in-law who experience live with in-laws. This study uses qualitative methods with in-depth interview. Participants are three husbands as son-in-law who live with their spouse and in-laws. The results showed that some aspects of psychological well-being, such as autonomy and environmental mastery appeared. In addition, social support from wife has played an important role, especially in helping husbands to adapt when living with in-laws.